Serum Levels of Sirtuin-1 in Patients with Lung Cancer and its Association with Karnofsky Performance Status: Sirtuin-1 in lung cancer - Hosseninia, Saeed; Ameli, Aslan; Aslani, Mohammad Reza; Pourfarzi, Farhad; Ghobadi, Hassan (Acta Biomedica Atenei Parmensis, 2021)
Background: Lung cancer is a major cause of cancer-related deaths worldwide. There are conflicting results regarding the role of sirtuin-1 in cancer. This study aimed to evaluate the serum sirtuin-1 levels in patients with lung cancer and its relationship with the quality of life based on Karnofsky performance statue scale (KPS). Methods: Serum sirtuin-1 levels were measured in 30 male patients with lung cancer and 50 healthy men. The two groups were matched for age. The difference between the serum levels of sirtuin-1 between the two groups and its relationship with KPS and other clinical parameters were evaluated. Data were analyzed by independent t-test and Pearson correlation, and P < 0.05 was considered as significant. Results: Sirtuin-1 levels were significantly lower in the patients in comparison with healthy subjects (P < 0.001). There was also a significant relationship between the serum level of sirtuin-1 with KPS (P < 0.001, r = 0.634), arterial oxygen saturation (P < 0.01, r = 0.470), and smoking history (P < 0.01, r = -0.330). In addition, the serum sirtuin-1 levels were significantly lower in adenocarcinoma than that in squamous cell carcinoma or small cell lung cancer (p < 0.001 and P < 0.05, respectively). Conclusion: The serum levels of sirtuin-1 were lower in patients with lung cancer. In addition, there was a significant correlation between serum levels of sirtuin-1 and KPS, O2 saturation, and smoking history. Further serological and histological studies seem to be necessary due to the existence of conflicting reports regarding sirtuin-1.